STUDENT’S COMPETITIVE RESOURCE IN A REGIONAL UNIVERSITY - Vladimir V. Baranov; Izabella D. Belonovskaya; Yuliya N. Nikulina (Высшее образование в России)
The article is devoted to the phenomenon of competitive resource for a university graduate. The pedagogical and sociological aspects of its formation in the regional university complex are presented. On the basis of factor analysis the opinions of various stakeholders on the significant competitive advantages of graduates on the regional labor market are explored. As a pedagogical tool to create student’s competitive resource at Orenburg State University was developed a special program, including employment training courses, sports and context games, corporate health groups, special skills raising courses for teachers, curators, and elective disciplines for masters of pedagogy.